TIME RISK ANALYSIS OF IMPLEMENTATION SELF-MANAGED COMMUNITY PROJECT IN BANGIL – KALIANYAR VILLAGE - Luqman Cahyono; Mirna Apriani; Anggara Trisna Nugraha; Agung Prasetyo Utomo (LPPM Universitas Negeri Jakarta, 2022)
Self-managed project through of KOTAKU (Kota Tanpa Kumuh) program managed by Lembaga Keswadayaan Masyarakat Abdi Karya Amanah Kalianyar - Bangil Village received around 1 billion funds from Direktorat Jenderal Cipta Karya Kementrian Pekerjaan Umum Dan Perumahan Rakyat. The implementation of self-managed projects is carried out entirely by the community with less knowledge regarding building construction. The research objective is to identify and analyze time risks in implementing community self-managed projects. The data analysis method used is literature study, observation, average analysis, risk analysis and risk matrix preparation. The results of the analysis show that there are 20 risk variables with the highest ranking being low labor productivity where the measurement scale is likely to occur >60–80% and the risk impact on time is >7-30 days from the duration of the project, then the risk response decision